Heuristic and Hermeneutic Reading of 75 Kufic Towards Ramadan FOKS Indonesia: a Study in Riffaterre’s Semiotics - Adib Alfalah; Asep Sopian (International Journal of Emerging Issues in Islamic Studies, 2024)
In the current era of digital development, Muslim societies have unique and impactful ways of welcoming Ramadan; for instance, "75 Kufic Towards Ramadan" was initiated by the Friends of Kufic Square Indonesia (FOKS Indonesia) community. This welcome enhances the daily posting of Kufic works on social media for 75 days leading up to Ramadan. However, sometimes ordinary people find reading and understanding posts difficult, even though they contain meaning. Therefore, based on this issue, this research aims to describe the heuristic and hermeneutic reading of the collection of calligraphic works, “75 Kufic Towards Ramadan”. This study adopts a qualitative descriptive approach, employing content analysis techniques, with data collected through observation, interviews, and documentation, focusing on Kufic texts shared in the "75 Kufic Towards Ramadan" series on FOKS Indonesia's official Instagram account (@foksindonesia). Subsequently, this data was analyzed using the heuristic and hermeneutic analysis techniques in Michael Riffaterre's semiotics. This study's findings are presented as an explanation of the heuristic and hermeneutic reading of the “75 Kufic Towards Ramadan” Kufic texts. Among these Kufic texts created by Kufiers are pieces of verse from the Quran, Hadith, and Mahfudzat in Arabic. These Kufic texts essentially represented deep feelings of joy for the Muslim community in welcoming Ramadan, which is full of glory and forgiveness. Consequently, people could receive positive messages and impressions when welcoming the month of Ramadan.